Ketahanan Mortar Campuran Serbuk Karet Terhadap Suhu Tinggi - Widya, Diah; Djauhari, Zulfikar; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The growing of automotive industry along with the increasing need for tire production cause to many waste tire. To solve this problem, many innovative solution have been proposed, namely the use of rubber tires as an added material in the manufacture of concrete mixture This is due to its flexible nature so as to increase the ductility of concrete. This research aims to study how compressive strength of mortar are resistant to high temperatures with materials added to waste tire used in powder form. Variations in the content of rubber powder used were 0%, 2.5%, and 5% of the weight of cement. Mortar was burned at temperatures of 250ºC, 500ºC, and 750 ° C for 3 hours. The results of the research and compressive strength with room temperature showed that OPC with the addition of 5% rubber powder had the highest compressive strength of 18.20 MPa. But when the mortar experienced a temperature higher than 250 ° C, the mortar strength decreased by 10%, with the addition of tire rubber powder as much as 5% with a compressive strength of 15.92 MPa, making the mortar had a better compressive strength than without the addition of powder rubber. Moreover the optimum temperature in mortar testing was at a temperature of 500 ° C with 5% rubber powder mixture. OPC mortars that were burned at 500 ° C and 750 ° C experience a hair cracking the mortar surface.Keywords:, Rubber powder, mortar, OPC, high temperature.